A new phenotyping method for root growth studies in compacted soil validated by GWAS in barley - Giorgia Carletti; Agostino Fricano; Elisabetta Mazzucotelli; Luigi Cattivelli (Plant Methods)
Abstract Background Soil compaction is defined as the reduction of air-filled pore space affecting soil density, water conductivity and nutrient availability. These conditions negatively influence root morphology, root development and plant growth leading to yield loss. To date, the ability of roots to penetrate compacted soil has been investigated using high density agar or wax-petrolatum layers as a proxy for compaction. Nevertheless, these methods are not realistic and fail to account for the root-soil interaction that influences root growth ability. Results Artificially compacted soil lumps were prepared using natural field soil mixed with sand and vermiculite in a 1:1:0.2 ratio and adjusted to a final water content of 31%. A Genome Wide Association Study (GWAS) was performed to validate this new methodology, combining a panel of 139 barley cultivars with a Single Nucleotide Polymorphism (SNP) dataset of 5,317 polymorphic markers. The panel was evaluated at seedling stage for four traits: total root length, average of diameter width, seminal root number, shoot: root weight ratio and two novel Quantitative Trait Loci (QTLs) associated with total root length were identified on Chr 4 H and 5 H. Four genes (a Nitrate Transporter1 (NRT1)/Peptide Transporter (PTR) family protein 2.2, a Hedgehog-interacting-like protein, an expansin and a cyclic nucleotide-gated channel) were hypothesized as plausible candidates for further investigation, given their implication in root development. In addition, the new phenotyping method revealed an altered plagiogravitropism phenomenon in barley during root emergence in compact substrates. In uncompacted soil, only the primary root exhibits vertical gravitropic set-point angle while a variable number of embryonic seminal roots develop with a shallower growth angle. In contrast, in compacted substrate all roots developed vertically to restore the growth angle after reaching a length of 4–5 millimetres. Conclusions A methodology based on root-soil interaction is presented as a new method for root growth evaluation and genomic studies in seedlings growing in compacted soil.